(3faGFS GdYfGUQ deLGdS Gdedc GdfGUQs - (3eMeO Hf WdMIs ((3eMeO Hf TcQ GdeGdci s)
(3ChdgG (B:s
(3GdMeO ddg GdPi aVd edhc GdCfGe Ydi cKjQ ef YHGOg JaUjdkG hHYO aEf Chdi eG JWdYJ Ydjg CacGQ Gdedhc GdJi gi edhc GdCacGQ s
(3BNQgG (B:s
(3hgPg ef edGFcJg GdeShejf HLfO jchfhf ef CfUGQg hLfhOg hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs